Morphometric Analysis of Mandibular Canal Variations Using CBCT andIts Clinical Implications in Implant Dentistry: A Cross-Sectional Study (Bangladesh Journal of Medical Science, 2026)
Background Precise three-dimensional assessment of the mandibular canal is essential before posterior mandibular implant placement because variations in canal course, terminal branching, and proximity to the alveolar crest may increase the risk of inferior alveolar nerve injury. Methods This cross-sectional cone-beam computed tomography (CBCT) study evaluated 240 mandibular scans of adults aged 20-70 years. Bilateral measurements were made at the second premolar, first molar, and second molar regions. Canal-to-crest distance, canalto- buccal cortex distance, canal diameter, anterior loop length, bifid canal prevalence, and implant-related risk zones were recorded. Interobserver reliability was assessed using intraclass correlation coefficients. Results The mean age was 42.8 ± 12.6 years, with 126 males (52.5%) and 114 females (47.5%). Mean canal-to-crest distance reduced posteriorly from 17.64 ± 2.92 mm at the second premolar to 13.21 ± 2.76 mm at the second molar (p